Proposed integrated hazardous waste management facility for National Capital Region, Philippines - Doctor, Diosdado C.
Disposal of hazardous waste in the Philippine is regulated by Republic Act 6960, otherwise known as Toxic Substances, Hazardous Wastes and Nuclear Waste Control Act of 1990. The Department of Environment and Natural Resources (DENR), being one of the implementing agencies however has failed to fully implement the law. One of the reasons is the absence of a hazardous waste management facility to recycle, treat and dispose hazardous waste. A study was conducted to determine what facilities and corresponding capacities should an integrated hazardous waste management facility must have to recycle, treat (including thermal) and dispose the waste generated in National Capital Region (NCR).